Intact attentional orienting towards inverted faces revealed by both manual responses and eye‐movement measurement in individuals with Williams syndrome. Issue 10 (1st August 2016) - Hirai, M.; Muramatsu, Y.; Mizuno, S.; Kurahashi, N.; Kurahashi, H.; Nakamura, M.
Abstract: Background: Individuals with Williams syndrome (WS) exhibit atypical attentional characteristics when viewing faces. Although atypical configural processing of faces has been reported in WS, the relative strengths of configural and local feature information to capture visual attention in WS remains unclear. We previously demonstrated that attentional capture by target‐unrelated upright faces differs depending on what response is measured. Whereas eye movements reflected subtle atypical attentional properties at the late stage of visual search, manual responses could not capture the atypical attentional profiles towards target‐unrelated upright faces in individuals with WS. Here we used the same experimental paradigm to assess whether sensitivity to configural facial information is necessary for capturing attention in WS. Methods: We measured both eye movements and manual responses from 17 individuals with WS and 34 typically developing children and adults while they were actively involved in a visual search task with an inverted face distractor. Task measures (reaction time and performance accuracy) and gaze behaviour (initial direction of attention and fixation duration) were analysed for each stimulus. Results: When the target and the inverted face were displayed in the same search array, reaction times and accuracies in individuals with WS showed similar tendencies as typical controls. Analysis of task and gaze measures revealed that attentional orienting towards inverted faces was not atypical. Conclusion: Although individuals with WS exhibited atypical gaze behaviour towards upright faces in our previous study, this unusual behaviour disappears if the faces are upside down. These findings suggest that local feature information alone (e.g. eyes) does not contribute to the heightened attention to faces, but configural information appears necessary for drawing attention to faces in individuals with WS, at least in the current experimental paradigm.